2008
DOI: 10.1155/2008/195427
|View full text |Cite
|
Sign up to set email alerts
|

Mycoplasma genitalium Lipoproteins Induce Human Monocytic Cell Expression of Proinflammatory Cytokines and Apoptosis by Activating Nuclear Factor κB

Abstract: This study was designed to investigate the molecular mechanisms responsible for the induction of proinflammatory cytokines gene expression and apoptosis in human monocytic cell line THP-1 stimulated by lipoproteins (LPs) prepared from Mycoplasma genitalium. Cultured cells were stimulated with M. genitalium LP to analyze the production of proinflammatory cytokines and expression of their mRNA by ELISA and RT-PCR, respectively. Cell apoptosis was also detected by Annexin V-FITC-propidium iodide (PI) staining and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
20
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 35 publications
2
20
0
1
Order By: Relevance
“…Like other Mollicutes, M. genitalium contains a significant proportion of lipoproteins in the cell membrane (45), consistent with the identification of 21 putative lipoprotein genes in the 580-kb genome (15). It has been shown recently that Triton X-114 preparations of detergent-soluble components from M. genitalium upregulate transcription of tumor necrosis factor alpha, interleukin-1␤ (IL-1␤), and IL-6 mRNA in the human THP-1 monocytic cell line (46,47), suggesting that lipoproteins may, at least in part, be responsible for immune activation. Of the 21 putative lipoprotein genes, we selected MG309 for inflammatory characterization because it is expressed during M. genitalium infection and is recognized by sera of M. genitalium patients, suggesting immune recognition by the host (L. Ma and D. H. Martin, unpublished findings).…”
supporting
confidence: 66%
“…Like other Mollicutes, M. genitalium contains a significant proportion of lipoproteins in the cell membrane (45), consistent with the identification of 21 putative lipoprotein genes in the 580-kb genome (15). It has been shown recently that Triton X-114 preparations of detergent-soluble components from M. genitalium upregulate transcription of tumor necrosis factor alpha, interleukin-1␤ (IL-1␤), and IL-6 mRNA in the human THP-1 monocytic cell line (46,47), suggesting that lipoproteins may, at least in part, be responsible for immune activation. Of the 21 putative lipoprotein genes, we selected MG309 for inflammatory characterization because it is expressed during M. genitalium infection and is recognized by sera of M. genitalium patients, suggesting immune recognition by the host (L. Ma and D. H. Martin, unpublished findings).…”
supporting
confidence: 66%
“…the same exercise (Rockel and Hartung, 2012) was done for peptidoglycan (9 publications, two using the whole blood MAt) and synthetic, recombinant, or isolated lipoproteins (8 publications, none using the whole blood MAt, i.e., (Wang et al, 2002;Schromm et al, 2007;McCurdy et al, 2003;Schroder et al, 2004;Sieling et al, 2003;Wu et al, 2008;DiRita et al, 2000;Giambartolomei et al, 2002). Note that PGN and muropeptides synergize with lPS and ltA in the whole blood MAt (traub et al, 2006;Holtkamp et al, 2010), which is not seen in the Bet.…”
Section: Evidence For Peptidoglycan and Muropeptide Detection In The mentioning
confidence: 99%
“…Mycoplasmal lipoprotein-induced NF-B expression has been linked to the production of cytokines and chemokines, which can be detected both in vitro and in vivo and results in inflammation in experimental animals (20,31). Another downstream effect of NF-B activation is the induction of apoptosis of affected cells, and mycoplasmal lipoproteins have been shown to induce this form of cell death in vitro (37,39). However, Gerlic et al (11) have shown that M. fermentans total lipoproteins and the synthetic lipopeptide MALP-2 have an antiapoptotic effect on U937 cells.…”
Section: Vol 78 2010mentioning
confidence: 99%